Terminal Internasional Pelabuhan Penumpang Tanjung Harapan Di Kabupaten Kepulauan Meranti Dengan Pendekatan Arsitektur Kontemporer - Safitri, Elvi; Hidayat, Wahyu; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
International Port Passenger Kepulauan Meranti Regency is part of TanjungHarapan with the application of contemporary architecture is a public facility thataccommodates marine transportation activities. The development of sea transport facilities in line with the development of a contemporary architecture that is both innovative and flexible, well out of shape or display as well as the use of materials that will support the display of contemporary architectural style. The design aims to support the activities of sea transport that supports the needs of the present and the future, become the driving force for potentialterritory Kepulauan Meranti Regency Research methods used include field data collection, studies, and empirical studies library. The results of this research to design an internationalstandard building with wave concept and contemporary architecture application in terms of shape, color neutral buildings, the use of a flexible material and create something innovative markedly on the building to suit the times.Key words: Contemporary, International Port Passenger, Kepulauan Meranti, Wave